Fatigue life extension of epoxy materials using ultrafast epoxy-SbF5 healing system introduced by manual infiltration - X. J. Ye; Y. Zhu; Y. C. Yuan; Y. X. Song; G. C. Yang; M. Z. Rong; M. Q. Zhang (eXPRESS Polymer Letters)
The present paper is devoted to the verification of the capability of epoxy-SbF5 system as a healing chemistry for rapidly retarding and/or arresting fatigue cracks in epoxy materials at room temperature. Owing to the very fast curing speed of epoxy catalyzed by SbF5, epoxy monomer and the hardener (ethanol solution of SbF5–ethanol complex) are successively infiltrated into the fracture plane under cyclic loading during the tension-tension fatigue test. As a result, the mechanisms including hydrodynamic pressure crack tip shielding, polymeric wedge and adhesive bonding of the healing agent are revealed. It is found that the healing agent forms solidified wedge at the crack tip within 20 s after start of polymerization of the epoxy monomer, so that the highest healing effect is offered at the moment. The epoxy-SbF5 system proves to be effective in rapidly obstructing fatigue crack propagation (despite that its cured version has lower fracture toughness than the matrix), and satisfies the requirement of constructing fast self-healing polymeric materials.